Inflation Targeting Under Potential Output Uncertainty - Gaiduch, Victor (IMF Working Papers; Working Paper, 2000)
To achieve their price stability objectives, many monetary authorities use the gap between current and potential output as an indicator of future price pressures. This policy-setting strategy has been criticized because potential output estimates have a high degree of uncertainty. In this paper, estimates of potential output uncertainty in New Zealand are used to examine the output gap's usefulness. The results suggest that although output gap uncertainty leads to more inflation and output variability, policy based directly and/or indirectly on the output gap leads to better macroeconomic stability than policy based only on observable inflation and output growth.